2011
DOI: 10.1200/jco.2011.29.7_suppl.87
|View full text |Cite
|
Sign up to set email alerts
|

CyberKnife for prostate cancer: Is it cost-effective?

Abstract: 87 Background: The study assessed the cost-effectiveness of CyberKnife (CK) compared to surgery and radiation therapy for the treatment of prostate cancer (PC) from a third-party and societal perspective. Methods: For patients > 65 yrs with localized PC, a Markov model compared treatment with CK, intensity modulated radiation therapy (IMRT), surgery or proton therapy (PT). Following treatment, patients were at risk of long-term toxicity: genitourinary (GU); gastrointestinal (GI); and sexual dysfunction (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…With most radiation oncologists using IMRT in the treatment of low‐risk prostate cancer, costs for this relatively indolent disease have increased. A recent American Society of Clinical Oncology abstract using Markov modeling suggests that the total life‐time cost of using the CyberKnife is significantly lower than that of IMRT ($25,904 vs $38,915) 5. That model also projects higher quality‐adjusted life‐years for CyberKnife compared with IMRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With most radiation oncologists using IMRT in the treatment of low‐risk prostate cancer, costs for this relatively indolent disease have increased. A recent American Society of Clinical Oncology abstract using Markov modeling suggests that the total life‐time cost of using the CyberKnife is significantly lower than that of IMRT ($25,904 vs $38,915) 5. That model also projects higher quality‐adjusted life‐years for CyberKnife compared with IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the possibility of decreased recurrence risk, hypofractionation, because of the larger doses delivered per individual treatment, allows for the deposition of dose biologically equivalent to the standard, multiweek regimens over a shorter period of time; for elderly patients with prostate cancer who have difficulties traveling, this has obvious quality‐of‐life (QOL) benefits. Finally, truncating treatment time may carry with it cost benefits compared with now widely adopted, longer course, intensity‐modulated radiation therapy (IMRT) regimens 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations models have shown that wage costs outweigh the cost of machines due to the labor-intensive nature of RT planning and delivery. 13-16 Moreover, although treatment planning complexity is increasing with evolving technology, the planning is only done at the beginning of therapy while cost builds with the delivery of each fraction. 17 Kesteloot et al 18 estimated that staffing RT facilities accounts for 50% of their cost.…”
Section: Introductionmentioning
confidence: 99%
“…The significant reduction in treatment course afforded by SBRT results in overall savings. The mean cost of conventional intensity-modulated RT (IMRT), $29,356,64 is higher than the estimated cost of robotic arm SBRT, between $19,275 and $24,873 55,58,65,66. Parthan et al compared the cost-effectiveness of IMRT with SBRT and proton-beam therapy using the Markov model, assuming equal long-term efficacy.…”
Section: Theoretical Benefits Of Robotic Arm Vs Gantry Sbrtmentioning
confidence: 99%